ISTIQAMAH AS A MEDIATOR IN THE BDI MODEL: IMPACT ON MIDDLE-CLASS BUSINESS VENTURES IN THE CULINARY SECTOR - Ramadhani, Nirma; Razak, Syaparuddin; Farida, Ida (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This study analyzes the role of istiqamah (steadfastness) as a mediator in the BDI (Belief, Desire, Intention) model for establishing culinary businesses among the middle class. The research addresses the low sustainability rate of middle-class culinary ventures, possibly due to limited spiritual values like istiqamah in business practices. The study hypothesizes that istiqamah can strengthen intentions and decisions to start and sustain culinary businesses. Using a quantitative survey and path analysis, data were gathered from 151 middle-class respondents in Bone Regency through structured questionnaires that measured belief, desire, intention, istiqamah, and business decisions. Data analysis with Structural Equation Modeling (SEM) examined the proposed mediation model. The results show that istiqamah significantly influences the decision to start a culinary business and mediates the relationship between intention and business decisions. Additionally, intention mediates the relationship between belief and desire with istiqamah, ultimately impacting business decisions. This study underscores the importance of integrating spiritual values into business practices, especially within the culinary sector. It contributes to the literature on spirituality in business and offers practical insights for entrepreneurs and policymakers in designing sustainable, ethical business strategies to address evolving economic challenges.